European integration in crisis? Of supranational integration, hegemonic projects and domestic politics. (December 2016) - Bulmer, Simon; Joseph, Jonathan
The European Union is facing multiple challenges. Departing from mainstream theory, this article adopts a fresh approach to understanding integration. It does so by taking two theoretical steps. The first introduces the structure–agency debate in order to make explicit the relationship between macro-structures, the institutional arrangements at European Union level and agency. The second proposes that the state of integration should be understood as the outcome of contestation between competing hegemonic projects that derive from underlying social processes and that find their primary expression in domestic politics. These two steps facilitate an analysis of the key areas of contestation in the contemporary European Union, illustrated by an exploration of the current crisis in the European Union, and open up the development of an alternative, critical, theory of integration.